BIOF–HILO Assay: A New MALDI–TOF Mass Spectrometry Based Method for Discriminating Between High- and Low-Biofilm-Producing Candida parapsilosis Isolates - De Carolis, Elena; Soldini, Silvia; La Rosa, Marilisa; Nucci, Fabio; Posteraro, Brunella; Sanguinetti, Maurizio (Frontiers in Microbiology, 2019)
Candida parapsilosis is the most frequent cause of catheter-related candidemia among non-Candida albicans species. This may be related to intrinsic capabilities as adhering and forming a biofilm on abiotic surfaces such as on medical devices. As previously demonstrated, patients infected with high biofilm-producing C. parapsilosis isolates had a greater mortality risk compared to patients infected with low biofilm-producing C. parapsilosis isolates. We developed the BIOF–HILO assay, a MALDI–TOF mass spectrometry (MS)-based assay, which compares mass spectra obtained from attached and suspended isolate cells during the early (i.e., 3-h) adhesion phase of in vitro biofilm formation. The composite correlation index (CCI) analysis was used to discriminate between mass spectra differences of the two cell types, classifying all 50 C. parapsilosis clinical isolates, included in the study, after only 3-h of testing, in high or low biofilm producers. All high (n = 25) or low (n = 25) biofilm producers had, according to CCI mass spectra comparison values, higher or lower than one CCI ratios, which were obtained by dividing the CCIsuspended cells by the CCIattached cells. In conclusion, the BIOF–HILO assay allows a rapid categorization of C. parapsilosis clinical isolates in high or low biofilm producers. This information, if timely provided to physicians, may improve treatment outcomes in patients with C. parapsilosis candidemia.